Carbohydrate Antigens as Potential Biomarkers for the Malignancy in Patients with Idiopathic Deep Venous Thrombosis： A Retrospective Cohort Study - 于淼 王运红 刘文奇 梅菲 王剑 欧阳晨曦 李毅清 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
A variety of biomarkers have been identified in recent prospective and retrospective re- ports as being potentially predictive of venous thromboembolis （VTE）, particularly idiopathic deep venous thrombosis （IDVT）. This study identified a serum tumor biomarker for early screening of IDVT. A total of 128 IDVT patients （54 females and 74 males; average age： 50.9＋17.4 years） were included. Carcinoembryonic antigen （CEA）, ferritin, β2-microglobulin, cancer antigen （CA） 125, CA 15-3, CA 19-9, squamous cell carcinoma antigen （SCC）, alpha-fetoprotein （AFP）, prostate specific antigen （PSA）, free PSA （f-PSA）, and beta-human chorionic gonadotropin （13-HCG） in patients with IDVT were detected. Malignancies were histo- or cytopathologically confirmed. Of the 128 IDVT patients, 16 （12.5%） were found to have malignarteies. Serum CEA, CA 125, CA 15-3, and CA 19-9 were found to be helpful for detecting malignancies in IDVT patients. Our study revealed a positive association between these markers and tumors in IDVT patients. On the other hand, SCC and AFP were not sensitive enough to be markers for detecting tumors in patients with IDVT. No significant differences were found in positive rates of ferritin and 132-microglobulin between turnor and non-ttmaor groups, and no significant difference exists in serum levels of ferritin and 132-microglobulin between the two groups. Carbohydrate antigens, CA 15-3 in particular, may be useful for differential diagnosis and prediction of malignancies in patients with IDVT.